An experimental and theoretical analysis of projectile and target geometry effects on ballistic limit velocity / M. Amiri - M., Amiri (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
FRP (Fibre Reinforce Plastics) laminates are now widely used in different industries like aviation, marine and transportation as FRP has shown considerable strength and hardness. However, these materials are vulnerable to lateral intensive static loads and impacts but have proved a good stability and strength in industrial applications. In this paper an analytical method for ballistic impact on FRP laminates has been proposed along with impact analysis of the panel, which has been carried out in two stages; Rupture and Wave-dominated local failure. First a simple analytical model for local deformation failure and critical shear failure has been used to predict perforation in FRP laminates. For verification of the model, several projectile impact experiments have been conducted to evaluate proposed model. It is concluded that experimental data are in good agreement with proposed analytical model results and effects of different geometrical parameters like panel dimensions and projectile diameter on ballistic velocity have been studied. In addition, analytical data have also been verified with results which were obtained from of LS-DYNA simulation.